Economic sustainability analysis of the specialty coffee farmers in Garça/SP - Campos, Amanda dos Santos Negreti; Satolo, Eduardo Guilherme [UNESP]; Mac-Lean, Priscilla Ayleen Bustos [UNESP]; Braga Júnior, Sérgio Silva [UNESP] (Coffee Science, 2021)
In the face of new market opportunities, farmers can increase the value of the product. This is in Short Food Supply Chains (SFSCs) based on the valuof origin and tradition. Farmers use this valuation as a product differentiation that improves their economic Sustainability. Therefore, this work aims tanalyze the economic Sustainability of specialty coffee farmers in Garça, Sao Paulo State (Brazil), after participating in SFSCs. For this reason, the researcapproach was qualitative and quantitative, with the study of several cases and the application of the semi-structured form with farmers. Data analysidescriptive statistics, and Wilcoxon Rank-Sum Test were used. The results indicated the introduction of farmers in new markets, various distribution formand the addition of product varieties and premium prices, which contributed to profitability. Infrastructure costs, however, were expensive. One of thcontributions of this study is to describe the specialty coffee supply chain when it is sold directly for consumption, shifting from the traditional coffemarket to short chains, contributing to the literature, and the farmers in a country with limited financial resources addressing an improvement of income.
Keywords: Alternative food networks; Direct farm marketing; Direct sales; Economic local; Territory